Express in action writing, building, and testing Node.js applications - Hahn, Evan (Manning Publications, 2016)
Express in Action is a carefully designed tutorial that teaches you how to build web applications using Node and Express. About the Technology Express.js is a web application framework for Node.js. Express organizes your server-side JavaScript into testable, maintainable modules. It provides a powerful set of features to efficiently manage routes, requests, and views along with beautiful boilerplate for your web applications. Express helps you concentrate on what your application does instead of managing time-consuming technical details. About the Book Express in Action teaches you how to build web applications using Node and Express. It starts by introducing Node's powerful traits and shows you how they map to the features of Express. You'll explore key development techniques, meet the rich ecosystem of companion tools and libraries, and get a glimpse into its inner workings. By the end of the book, you'll be able to use Express to build a Node app and know how to test it, hook it up to a database, and automate the dev process. What's Inside Simplify Node app setup with Express Testing Express applications Use Express for easy access to Node features Data storage with MongoDB Covers Express 4 and Express 5 alpha About the Reader To get the most out of this book, you'll need to know the basics of web application design and be proficient with JavaScript. About the Author Evan Hahn is an active member of the Node and Express community and contributes to many open source JavaScript projects.
Includes index. - Online resource; title from title page (Safari, viewed May 9, 2016)
Keywords: Node.js; Application program interfaces (Computer software); JavaScript (Computer program language); Application software -- Development; Internet programming; Interfaces de programmation d'applications; JavaScript (Langage de programmation); Logiciels d'application; Développement; Programmation Internet; APIs (interfaces); Application software; Development